The Differences of Haemoglobin changes between two methods of IFA Supplementations among Anemic Female Adolescent Students of Miftahul Huda Al Azhar Langgensari Islamic Boarding School, West Java - Syabilila Indraswari; Endang L Achadi (Indonesian Journal of Public Health Nutrition, 2020)
AbstractFemale adolescent student s in boarding schools are vulnerable in having anemia due to packed sched ule and limited animal source food. The aim of t his research was to compare the differences of haemoglobin level after weekly Iron Folate Acid (IFA) tablet supplementation and weekly plus daily IFA tablet supplementation during menstruation for 8 week of intervention among anemic students . This study use d qu asi experimental non equivalent control group design. A total of 40 anemic respondents was selected in this study , 20 of them received a weekly IFA tablet s upplementation (treatment 1 group), and the 20 other respondents received weekly plus daily during their menstruation (treatment 2 group). The first hemoglobin measurement and other variables were obtained prior to intervention. Around 52% of all 278 eligible students were anemic at the start of the study. Of the anemic selected sample, 2 of them left the boarding school in the middle of the study because they were ill. A t the end the study 23 out of 38 anemic samples (60.5%) became non anemic. There was a significant increase of haemoglobin level in both groups after the interventio n (both group s have p value < 0.01). This increase was not significant ly different between the two interventions (p = 0.797). This study prove d that weekly supplementation was as effective as weekly plus daily supplemen tation during menstruation in increasing Haemoglobin (Hb ) level among anemic students.AbstrakSantri remaja putri rentan terkena anemia karena kegiatan yang padat dan kurang nya asupan zat gizi terutama makanan sumber pangan hewani . Penelitian ini dilakukan untuk mengetahui perbandingan antara dua program suplementasi tablet tambah darah yang terdiri dari zat besi dan asam folat (TTD), yaitu yang diberi satu tablet per minggu (group perlakuan 1) dan yang diberi satu tablet per minggu ditambah satu tablet sehari saat menstruasi selama 8 ming gu (group perlakuan 2 ) . Penelitian ini menggunakan d isain quasi experimental nonequivalent control group . Responden penelitian ini sebanyak 38 orang dimana 20 orang menerima suplementasi mingguan (2 orang kemudian meninggalkan pondok saat penelitian karena sakit ) dan 20 orang menerima suplementasi mingguan ditambah setiap hari saat menstruasi. Pengukuran data pengetahuan, menstruasi, status g izi, pola konsumsi inhibitor, enhancer dan protein hewani dilakukan sebelum intervensi, data suplementasi diukur setelah intervensi dan data kadar hemoglobin diukur saat sebelum dan sesudah intervensi. Pemeriksaan Hb pertama terhadap semua 278 siswa, seki tar 52% menderita Anemia. Diantara sampel siswa yang anemia, pada akhir intervensi 60.5%nya menjadi tidak anemia. Terjadi kenaikan kadar hemoglobin pada kedua kelompok setelah intervensi selama 8 minggu (kedua grup mempunyai nilai p < 0.01). Kenaikan tersebut tidak berbeda antara kedua kelompok perlakuan (p=0,797). Hasil penelitian ini membuktikan bahwa s uplementasi mingguan pada siswa yang menderita anemia memberikan efektivitas yang sama dalam meningkatkan kadar hemoglobin (Hb) darah dengan suplementasi mingguan ditambah harian selama menstruasi .